Association of trimethylamine oxide and its precursors with cognitive impairment: a systematic review and meta-analysis - Long, Caiyi; Li, Zihan; Feng, Haoyue; Jiang, Yayi; Pu, Yueheng; Tao, Jiajing; Yue, Rensong (Frontiers in Aging Neuroscience, 2024)
Objectives The role of trimethylamine oxide (TMAO) in patients with cognitive impairment remains controversial. This study aimed to assess the association between TMAO and its precursors and the prevalence of cognitive impairment. Methods PubMed, Embase, and Web of Science databases were searched for studies that met the inclusion criteria from their inception to 14 September 2024, and references were manually searched to identify any additions. Odds ratio (OR) was assessed by random-effects modeling, subgroup analyses to identify potential sources of heterogeneity, and the Newcastle-Ottawa Scale (NOS) and the Agency for Healthcare Research and Quality (AHRQ) Inventory for qualitative evaluation. Results Nine studies involving 82,246 participants were included in the analysis. Meta-analyses suggested that elevated TMAO levels were strongly associated with an increased risk of cognitive impairment (OR: 1.39, 95% confidence interval [95%CI]: 1.09–1.77, p < 0.05, I2:60%), and consistent results were obtained across all subgroups examined and sensitivity analyses. However, in the TMAO dose–response meta-analysis and TMAO precursor meta-analyses, the results were not significantly different (dietary choline: OR: 0.93, 95%CI: 0.78–1.10, p = 0.385, I2:68%, plasma choline: OR: 0.65, 95%CI: 0.41–1.02, p = 0.063, I2:76%, plasma betaine: OR: 0.74, 95%CI: 0.52–1.05, p = 0.094, I2:61%). Conclusion We found that high TMAO concentrations were positively associated with the risk of cognitive impairment. TMAO is expected to be a potential risk predictor and therapeutic target for cognitive impairment. However, more high-quality studies are needed to further investigate the dose relationship between circulating TMAO concentrations and cognitive impairment. Systematic review registration PROSPERO, identifier: CRD42023464543.